Oil and Gas in the Arctic: Legal Status and Reserves - N. N. Shvets; P. V. Beresneva (Vestnik MGIMO-Universiteta)
When researching such a hot topic as development of oil and gas reserves in Artie it's crucial to answer 3 key questions. What is legal status of Artie reserves and Russian offshore zone in Arctic? Are there any gaps in international lawthatinhibits oil and gas development? How big are Arctic oil and gas reserves? Are they well-explored? What are production costs of oil and gas in Artie? Is it profitable to develop reserves in Artie? The article addresses these vital questions with the detailed analysis. 1982 UN Convention on the Law of Sea partially regulates Artie legal status but countries apply sectorial principal to Arctic territories to claim their rights. There are few border disputes left. The borders of Russian outer continental shelf are shaped by international law and bilateral agreements and undergoing final review within UN processes and mechanisms. Arctic reserves'estimates do vary significantly as the region is barely explored. According to with a high 2008 US Geological Survey and 2006 Wood Mackenzie and Fugro Robertson study Arctic reserves are about 10-15% of global reserves. Most of them are offshore (around 85%), and gas accounts for 80% of reserves. Russia has more than a half of Artie reserves. Under International Energy Agency it's profitable to develop Arctic oil reserves as production costs ($40-100 bbl) are below current and 2035 forecast oil price. On the contrary, gas production is questionable from costs point of view. Gas market is projected to remain regional. With Artie gas production cost of$ 4-12 million BTU, there is no business case to develop Artie gas in America and at the edge of profitability in Europe.